How Taxes and Inflation Will Affect Economic Growth in ASEAN Emerging Markets - Ika Prajawati, Maretha; Eliza Syahda, Putri; S, Basir (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : The objective of this research is to examine the impact of tax revenue and inflation on the economic development of ASEAN emerging market nations from 2010 to 2023 Design/Methode/Approach : The analysis utilizes yearly secondary data acquired from diverse sources, including the World Bank, CEIC, and IMF. The chosen analytical technique is panel data regression, specifically the Random Effect Model (REM) approach, which was selected based on the Chow, Hausman, and Breusch-Pagan statistical tests. Research Finding : The research findings suggest that tax income has a detrimental and statistically significant impact on economic development. The findings suggest that fiscal and monetary policies have distinct effects on the economic development of ASEAN developing nations. Considerable tax revenue has the capacity to impede economic development, but modest inflation may stimulate economic growth Theoretical contribution/Originality :These findings enhance our knowledge of how macroeconomic factors affect economic growth in the ASEAN area. Practitionel/Policy implication : The significance of government action in controlling economic growth through taxation and inflation is supported by this study. Macroeconomic uncertainty may result in lower tax collection. This includes uncertainty about spending, investing, and saving. Economic activity is subsequently impacted, necessitating careful analysis. In order to lessen the detrimental effects on economic growth, particularly those on tax revenue and inflation, lessons learned from this study can be used to future financial crises and economic shocks. Research limitation : Due to inadequate data collection, this analysis eliminates the tax structure and is limited to looking at the tax revenue ratio. Future studies must clarify the tax systems of ASEAN countries in order to identify which taxes have a positive impact on economic growth and which have a negative one.